Effect of Economic and Legal Corporate social Responsibility on Firm’s Competitive Advantage among Selected Banks in Nairobi County, Kenya - Chirchir , Betty (African Journal of Education,Science and Technology (AJEST), 2021)
Globalization and stiff competition among industry players has resulted in a remarkable change in the way businesses run and operate, with the quest for excellence and all-round growth key objective of firms. Corporate Social Responsibility (CSR) has emerged as a view that can add to competitive advantage of a firm and suggests that corporate decision –making must take care of a range of social and environmental affairs in order to maximize long-term financial returns. To survive in the industries, firms are always trying to create competitive advantage. However, banks today are facing a myriad of challenges such as high employee turnover, technology change, and bad reputation among others that have threatened their competitive positions. The main purpose of this study was to investigate the effect of corporate social responsibility on firm Competitive Advantage among selected banks in Kenya. The objectives that this study focused on were; to establish the effect of economic and legal responsibility on organizational competitive advantage. The study was informed by stakeholders Theory by Freeman (1984). Explanatory Research Design was adopted in the study. The target population was 848 employees withdrawn from 25 banks within Nairobi city center. Simple random sampling was used to select a sample size of 183 employees. Questionnaire was a tool for data collection. Factor analysis was used to test content validity. The study used correlation, descriptive and inferential statistics. The study adopted multiple regression analysis to analyze data. The major findings from this study revealed that economic responsibility and legal responsibility and have positive relationship to firm competitive advantage. The findings from this study may benefit scholars and futures researchers who may use the findings to find out suggested areas to be researched on or make a comparative study. The investors may also use the findings to ascertain the ideal corporate social responsibility models viable to be considered when investing various projects bank and enable them evaluate the capital appraisal and avoid being distorted by unviable projects.